The Influence of Financial Literacy on Investment Decision In The Millennial Generation Post The Covid-19 Pandemic - Ray Burton; Irni Yunita (Jurnal Syntax Transformation, 2024)
The COVID-19 pandemic hit the world in late 2019, bringing many human activities to a halt. Several phenomena occurred as a result of these difficult conditions. Due to the rapid development of technology and the use of technology to earn income is new to some people, many people are exposed to fraud that occurs in the field of financial technology. This study aims to find out how people's financial literacy index, how they choose to invest, and how their financial literacy affects investment decisions. Since the millennial generation is the majority of productive age in Indonesia, this research targets the millennial generation. This research is limited to the Bandung City area because there are differences in Regional Minimum Wage (UMR) and investment decision-making behavior between cities. This verification quantitative research uses purposive sampling method with a total sample size of 1,275,520 people. Data was collected using an online questionnaire and the SPSS program was used to analyze the data of 400 respondents to find out how the level of financial literacy affects investment decisions and to identify all factors that affect financial literacy. The three factors used to measure the effect of financial literacy are financial knowledge, behavior and attitude. Descriptive statistics, normality, heteroscedasticity, multicollinearity and multiple linear regressions were the SPSS tests performed. This study found that financial knowledge, behavior and attitude together have a significant influence simultaneously on investment decisions. In addition, this study also found that financial knowledge, behavior and attitude each have a partially significant influence on investment decisions.